Carbopol emulgel loaded with ebastine for urticaria: development, characterization, in vitro and in vivo evaluation - Barkat Ali Khan; Arshad Ali; Khaled M. Hosny; Abdulrahman A. Halwani; Alshaimaa M. Almehmady; Muhammad Iqbal; Waleed S. Alharbi; Walaa A. Abualsunun; Rana B. Bakhaidar; Samar S. A. Murshid; Muhammad Khalid Khan (Taylor & Francis Group, 2022)
Urticaria affects all age groups of a population. It is triggered by allergens in foods, insect bites, medications, and environmental conditions. Urticaria is characterized by itching, a burning sensation, wheals and flares, erythema, and localized edema. The aim of this study was to develop a polymeric dosage form of ebastine using Carbopol 940 and mixture of span and tween. The emulsion was prepared, the gelling agent was added and the desired emulgel loaded with active drug was formulated. The formulations were subjected to physical stability, pH, viscosity, spreadability, drug content analysis, thermal analysis, in vitro drug release, and in vivo anti-allergic activity in animal model. The formulated emulgel exhibited good physical stability. The pH of the formulation was in the range of 5.2 ± 0.17 to 5.5 ± 0.20 which is suitable for topical application. Insignificant changes (p > .05) were observed in viscosity and spreadability of stored emulgels. The drug content was in the official limit of Pharmacopeia (i.e. 100 ± 10%). DSC measurements predicted that there is no interaction between the active moiety and excipients in emulgel formulation. The optimized formulation (ES3) released 74.25 ± 1.8% of ebastine after 12 h. The ebastine emulgel showed significant (p < .05; ANOVA) in vivo anti-allergic activity as compared to commercial product Benadryl® in histamine-induced allergy in rabbits. This study concluded that a topical drug delivery of ebastine-loaded emulgel could be well tolerated and safe for the treatment of urticaria/hives.